2011
DOI: 10.1111/j.1939-0025.2011.01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug abuse and intimate partner violence: A comparative study of opioid-dependent fathers.

Abstract: Because very little is known about the coparenting relationships of drug-abusing men, this comparative study was designed to examine the lifetime prevalence and recent frequency of intimate partner violence in the coparenting relationships of 106 fathers enrolled in methadone maintenance treatment. When compared with 118 community controls, the opioid-dependent fathers reported greater prevalence of physical, sexual, and psychological aggression directed at the mother of their youngest biological child over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 55 publications
6
42
0
1
Order By: Relevance
“…This limited body of research has shown that alcohol (Walker et al, 2012), marijuana (CDC, 2010b), and opioid (Moore et al, 2011) use are all risk factors for IPV victimization. Different mechanisms have been identified to help explain the influence of substance use on IPV victimization.…”
Section: Intimate Partner Violence and Substance Usementioning
confidence: 99%
“…This limited body of research has shown that alcohol (Walker et al, 2012), marijuana (CDC, 2010b), and opioid (Moore et al, 2011) use are all risk factors for IPV victimization. Different mechanisms have been identified to help explain the influence of substance use on IPV victimization.…”
Section: Intimate Partner Violence and Substance Usementioning
confidence: 99%
“…The large number of single mothers (78.9%) participating may be attributed to their being no partner to prevent them from seeking outside support. The significant number of fathers (albeit mothers report) 'using substances' (33.6%) does correlate with other findings (Easton, McMahon, & Moore, 2011). However, physical violence features at a significantly higher rate than in other studies measuring frequency and types of violence used (Coker, Smith, McKeown, & King, 2000).…”
Section: Discussionmentioning
confidence: 47%
“…Such roles may be particularly detrimental to mental HRQOL among HIV-infected women, who also have competing priorities to manage their own illness. In addition, alcohol and illicit drug use are well-documented to increase the risk of family violence, including intimate partner violence (IPV) (Abramsky et al, 2011; Choenni, Hammink, & van de Mheen, 2015; Moore, Easton, & McMahon, 2011), which may also contribute to poor mental HRQOL.…”
Section: Discussionmentioning
confidence: 99%